CD4 count‐based failure criteria combined with viral load monitoring may trigger worse switch decisions than viral load monitoring alone. Issue 2 (10th December 2015) - Hoffmann, Christopher J.; Maritz, Jean; van Zyl, Gert U.
Abstract: Objective: CD4 count decline often triggers antiretroviral regimen switches in resource‐limited settings, even when viral load testing is available. We therefore compared CD4 failure and CD4 trends in patients with viraemia with or without antiretroviral resistance. Methods: Retrospective cohort study investigating the association of HIV drug resistance with CD4 failure or CD4 trends in patients on first‐line antiretroviral regimens during viraemia. Patients with viraemia (HIV RNA >1000 copies/ml) from two HIV treatment programmes in South Africa ( n = 350) were included. We investigated the association of M184V and NNRTI resistance with WHO immunological failure criteria and CD4 count trends, using chi‐square tests and linear mixed models. Results: Fewer patients with the M184V mutation reached immunologic failure criteria than those without: 51 of 151(34%) vs . 90 of 199 (45%) ( P = 0.03). Similarly, 79 of 220 (36%) patients, who had major NNRTI resistance, had immunological failure, whereas 62 of 130 (48%) without (chi‐square P = 0.03) did. The CD4 count decline among patients with the M184V mutation was 2.5 cells/mm 3 /year, whereas in those without M184V it was 14 cells/mm 3 /year ( P = 0.1), but the difference in CD4 count decline with and without NNRTI resistance was marginal. Conclusion: Our data suggest that CD4 count monitoring may lead to inappropriate delayed therapy switches for patients with HIV drug resistance. Conversely, patients with viraemia but no drug resistance are more likely to have a CD4 count decline and thus may be more likely to be switched to a second‐line regimen.